Effectiveness of Inquiry Learning Model Based on Socio-Scientific Issues to Develop Students’ Critical Thinking Skills - Irawati, Sabrina Oktavia; Wulandari, Ria (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to describe the effect of the socio-scientific issue-based inquiry learning model on the critical thinking skills of eighth-grade students in the subject of the digestive system. Methodology: This study used a quantitative experimental method with a nonequivalent control group design. The population in this study was 320 eighth-grade students, with a sample size of 64 students. Data collection techniques used tests. The research instruments used pretest and posttest critical thinking skills. The data analysis technique in this study used N-gain (Normalized Gain) and inferential statistics in the form of an independent sample t-test. Main Findings: The main findings of this study indicate that the socio-scientific issues-based inquiry learning model significantly improves students' critical thinking skills compared to conventional learning with N-gain 0,94 in high category. The test results show a sig. value (2-tailed) = 0.021 (<0.05), which indicates a significant difference between the experimental and control classes. This model is effective because it involves students in scientific investigations based on real social issues that encourage them to think reflectively, analytically, and evidence-based in their decision-making. Novelty/Originality of this study: The novelty of this study lies in the application of a socio-scientific issues-based inquiry learning model to digestive system material to develop students’ critical thinking skills. The socio-scientific issues used are obesity and GERD. The socio-scientific issues-based inquiry learning model integrates scientific investigation with contextual and evidence-based social analysis.